Field trips to natural environments: how outdoor educators use the physical environment. Issue 3 (3rd July 2017) - Lavie Alon, Nirit; Tal, Tali
ABSTRACT: The main assumption of this study is that the natural environment is an important part of learning in out-of-school settings. We therefore aimed at understanding how outdoor educators (OEs) refer to, and use, the natural environment while guiding field trips, and how their use of the natural environment affects student learning outcomes. Using a mixed-method design, we studied 20 field trips to natural environments with respect to the content the OEs communicated to their students, the skills they taught, and the methods they used. The data we collected included observations of the 20 field trips, interviews with the OEs and their students, and 569 students' questionnaires. We found that the OEs often refer to scientific phenomena and concepts that can be seen outdoors, but they rarely attempt to develop values and attitudes. Eight types of learning outcomes were identified, of which structured active learning stood out as a practice that contributed to a variety of outcomes. Environmental action contributed to shaping students' attitudes and environmental behavior intentions. The thorough analysis we offer of the use of the natural environment could guide OEs pedagogy and, particularly, their use of the natural environment and could lead to further research in this field.